Answer:
Both statements (1) and (2) TOGETHER are sufficient to answer the question asked; but NEITHER statement ALONE is sufficient.
Step-by-step explanation:
Solving the equation of statement (1) with the quadratic formula:
[tex]x_{1,2}=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
[tex]x^2+40x+391=0\\x_{1,2}=\frac{-40\pm\sqrt{40^2-4(1)(391)}}{2(1)}\\x_{1,2}=\frac{-40\pm\sqrt{1600-1564}}{2}\\x_{1,2}=\frac{-40\pm\sqrt{36}}{2}\\x_{1}=\frac{-40+6}{2}=\frac{-34}{2}=-17\\x_{1}=\frac{-40-6}{2}=\frac{-46}{2}=-23\\[/tex]
In this equation, one of the values of x is bigger than -20 but the other is smaller, this statement doesn't give enough information to answer the question.
Solving the quadratic equation of the statement (2):
[tex]x^2=529\\x_{1,2}=\pm\sqrt{529} \\x_1=\sqrt{529}=23\\x_2=-\sqrt{529}=-23[/tex]
Again, one of the values of x is bigger than -20 and the other is smaller than -20. But if the information of this statement is considered along with the other x must be equal to -23, that is the value that appears as an answer in both equations, and with this information is possible to answer the question.